Relevansi Konsep Kafa'ah dalam Pemilihan Jodoh Masyarakat Modern Perspektif Hukum Keluarga Islam (Studi Kasus Desa Tlanakan, Kecamatan Tlanakan, Kabupaten Pamekasan) - Darta, Martinus; Mujiburrohman (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the relevance of the concept of kafa'ah in choosing a life partner in modern society based on the perspective of Islamic family law, focusing on the study in Tlanakan Village, Tlanakan District, Pamekasan Regency. This research is motivated by changes in society's views on the criteria for equality in marriage due to modern social developments, which have the potential to create differences in understanding between traditional values ​​and contemporary considerations in choosing a partner. This research is an empirical legal study with a sociological approach strengthened by normative legal analysis. Primary data were obtained through interviews with religious leaders, community leaders, and married couples, while secondary data came from literature on Islamic family law, fiqh munakahat, and the Compilation of Islamic Law. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate a shift in the meaning of kafa'ah from the dominance of lineage aspects to considerations of education, economics, and the independence of the couple. From the perspective of Islamic family law, the concept of kafa'ah remains relevant by placing religious equality as the main aspect, while social and economic aspects are flexible according to societal conditions and the goal of building a harmonious family